Damping of seismic vibrations of towers using a controlled reactive dampener - Ivanovich, Shein Alexander; Borisovich, Zaitsev Mikhail; Georgievich, Tamrazyan Ashot; Anatolyevna, Matseevich Tatiana (Journal of Structural Engineering, 2024)
The control of the dynamics of oscillatory movements with the help of active (reactive) dampers is considered. The principle of operation of a reactive damper is to create an alternating reactive force that prevents relative (bending) movements (oscillatory movements) of the structure at the right moments of time. It is shown that the process of activating the reactive damper from seismic impact on the structure is carried out by the triad “displacement – speed – electric drive of the damper”. Graphs of the dependence of the damper operation depending on thechange of individual parameters of the damper - the velocity of the jet Vgas, the duration of the jet Tgas, the maximum permissible relative deviation δmax. The analysis of the influence of these parameters on the efficiency of the damper is carried out. It is shown that a reactive damper with rationally selected parameters allows to reduce the level of mechanical vibrations of buildings and structures in conditions of non-stationary (seismic) impacts by 50-80%. A software tool has been developed that allows choosing the optimal parameters of a reactive vibration damper for this structure.